Taxonomy of compulsory and incentive legal consequences (legal measures) of committing illegal acts - Kozachenko, Oleksandr V.; Vasyliaka, Olesia K.; Chornozub, Larysa V.; Musychenko, Olha M. (Cuestiones Políticas, 2020)
The article is prepared for the purpose of publishing the results of scientific research obtained in the process of applying the taxonomic methodology for systematization of measures of legal influence. The methodology used the approaches of philosophical and legal theorization, a dog and systemic functional. One way of conclusion is proposed for the first time to use the taxonomies of legal measures. The study highlighted three aspects of legal measures: relational, predicate and functional. The relational manifestation of taxonomy allowed to identify the substrate of the external form of legal influence, which is the measure. It has been established that the form and method of legal influence is the dominant element of each legal measure. The predicative dimension of taxonomy allowed to form a taxonomic system of information in which the following taxonomic categories and taxa are distinguished: type - social events; subtype - legal measures; class - public and private legal measures; gender - separation of legal measures according to their sectoral affiliation; subgenre: the allocation of incentives and coercive measures; supervision - legal measures in their various forms and other measures that have no signs of legal liability.